Italy : Report on Observance of Standards and Codes-Fiscal Transparency Module Update. (IMF Staff Country Reports; Country Report, 2003)
During the 2003 Article IV Consultation mission, IMF staff reviewed developments in Italy's observance of fiscal transparency practices, with a view to updating changes in current practices, reviewing progress in implementing the initial report on observance and codes (ROSCs) recommendations, and identifying developments relevant for future observance of good fiscal transparency practices. The IMF staff recommendations in the first ROSC for Italy focused on the following four main areas: clarity of roles and responsibilities; public availability of information; open budget preparation, execution, and reporting; and assurances of integrity.